2012
DOI: 10.5551/jat.10694
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Analysis and Blood Flow Simulation of Basilar Artery

Abstract: Aim:The aim of this study was to find a region of low wall shear stress (WSS) in a basilar artery using 3-dimensional (3D) geometric analysis and blood flow simulation. Methods: A 61-year-old patient who underwent follow-up time-of-flight magnetic resonance angiography (TOF-MRA) of the brain was recruited as the subject of the present study. In the basilar artery, the angle of the directional vector was calculated for the region of low WSS. The subject's 3D arterial geometry and blood flow velocity from a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…It has been reported that vertebrobasilar artery tortuosity is associated with connective tissue disorders [18], reduced elasticity and degeneration of blood vessels, and vascular wall shear stress [3,19]. Vascular risk factors such as hypertension, diabetes and lipid metabolism disorders can promote atherosclerosis, aging, and degeneration of blood vessels, thereby aggravating vertebrobasilar artery tortuosity [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that vertebrobasilar artery tortuosity is associated with connective tissue disorders [18], reduced elasticity and degeneration of blood vessels, and vascular wall shear stress [3,19]. Vascular risk factors such as hypertension, diabetes and lipid metabolism disorders can promote atherosclerosis, aging, and degeneration of blood vessels, thereby aggravating vertebrobasilar artery tortuosity [20].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological features of the vertebrobasilar artery have been previously reported to have hemodynamic effects on brainstem infarction [16][17][18] . The hemodynamics of the BA are more effectively interpreted based on the two components of angulation, as these features determine the flow dynamics and rate of atherosclerotic progression 2) . In the present study, most of the subjects showed anterior angulation of the BA on the lateral view ( Table 1), such that the regions experiencing low wall shear stress along the lesser curvariation in the size of the vertebral arteries may affect the extent of lateral angulation, while the differences in the confluent angles from the vertebral arteries to the BA may influence the amount of anterior angulation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify and analyze hemodynamic information for the BA, we simplified the BA as triangles with two references (the vertebrobasilar junction and the division of the BA) and angulation points. Axial source images of the vertebrobasilar artery were obtained via TOF MR angiography and used to reconstruct multiplanar sections in the same screen, including the XZ (coronal) and YZ (sagittal) planes, with our own in-house code, as previously described 2) . Using the multiplanar sections, the two references and the most angulated points were selected and designated as three-dimensional (3D) Cartesian coordinates.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The low shear stress may result in altered physiological responses that include a decrease in endothelial nitric oxide synthase mRNA and protein expression,22 increased release of proinflammatory mediators such as macrophage chemoattractant-1,23 increased uptake of oxidized LDL,24 altered redox state of the vasculature, and altered smooth-muscle-cell gene expression 25. Regions of low arterial shear stress are considered to be vulnerable to future atherosclerotic growth26 and thrombosis evolution 2,3. However, the exact mechanisms underlying how low arterial shear stress affects neurovascular units and cerebrovascular networks need further evaluation 27…”
Section: Discussionmentioning
confidence: 99%